2018
DOI: 10.1152/ajprenal.00580.2017
|View full text |Cite
|
Sign up to set email alerts
|

Circadian regulation of kidney function: finding a role for Bmal1

Abstract: Mounting evidence suggests that there is an internal molecular "clock" within the kidney to help maintain normal renal function. Disturbance of the kidney circadian rhythm may pose a threat to water and electrolyte homeostasis and blood pressure regulation, among many other problems. The identification of circadian genes facilitated a more comprehensive appreciation of the importance of "keeping the body on time"; however, our knowledge is very limited with regard to how circadian genes regulate kidney functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
2
8
0
1
Order By: Relevance
“…Diurnal potassium rhythm is not well understood, but it has been suggested that the beneficial effects of potassium supplementation on BP were partly due to the resetting of potassium excretion rhythm, especially when the BP rhythm is lost due to salt-sensitive hypertension. 33 This change in diurnal potassium excretion contrasts with the diurnal rhythm of aldosterone excretion that remained intact and in phase with the light–dark cycle. Microarray analysis on mouse kidneys found that the majority of known potassium-regulatory genes were expressed in a circadian-dependent manner, including genes that encode Na + /K + ATPase, H + /K + ATPase, Kir1.3, ROMK, and the BK channel.…”
Section: Discussionmentioning
confidence: 93%
“…Diurnal potassium rhythm is not well understood, but it has been suggested that the beneficial effects of potassium supplementation on BP were partly due to the resetting of potassium excretion rhythm, especially when the BP rhythm is lost due to salt-sensitive hypertension. 33 This change in diurnal potassium excretion contrasts with the diurnal rhythm of aldosterone excretion that remained intact and in phase with the light–dark cycle. Microarray analysis on mouse kidneys found that the majority of known potassium-regulatory genes were expressed in a circadian-dependent manner, including genes that encode Na + /K + ATPase, H + /K + ATPase, Kir1.3, ROMK, and the BK channel.…”
Section: Discussionmentioning
confidence: 93%
“…BMAL1 is the main transcriptional activator of the circadian clock, which has been shown to regulate the progress of various renal diseases 7–10 . However, researches on its function in renal IRI are limited.…”
Section: Discussionmentioning
confidence: 99%
“…BMAL1 is the main transcriptional activator of the circadian clock, which has been shown to regulate the progress of various renal diseases. 7 , 8 , 9 , 10 However, researches on its function in renal IRI are limited. Previous studies have revealed that the expression level of BMAL1 in cardiac and cerebral tissues decreased significantly after IR, 17 , 28 , 29 which is in line with our study showing that renal IR causes a dramatic decrease in BMAL1 expression level in renal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Bmal1 stimulates transcription of numerous genes that have been linked to maintaining proper kidney function [25,26]. This relationship has also been shown in kidney-specific knockout mice where Bmal1 was knocked out specifically in renin-producing cells (Renin1dCre-positive).…”
Section: Sodium Handlingmentioning
confidence: 92%